УСОВЕРШЕНСТВОВАНИЕ ИНСТРУМЕНТАЛЬНОЙ НЕЙТРОННО-АКТИВАЦИОННОЙ МЕТОДИКИ АНАЛИЗА ЭЛЕМЕНТНОГО СОСТАВА - Журакулов, А.Р.; Курбанов, Б.И.; Музафаров, А.М.; Байчаев, Ф.Х. (SCIENCE and SOCIETY, 2025)
In this paper, the issues of reducing the analysis time when using the comparator method in neutron activation analysis (NAA) to determine the content of macro- and microelements in a substance are investigated.